Opportunities and Challenges for Scaling Up Geothermal Development in Latin America and the Caribbean - World Bank Group (World Bank, Washington, DC, 2018)
Geothermal energy can play a substantial role in meeting the energy needs of many Latin America and Caribbean Region (LAC) countries given the region’s vast potential. The majority of geothermal resources in the LAC region remain largely untapped, not only in Central America and Mexico where development is more advanced, but also in the Caribbean and in South America. If further explored and developed in a sustainable fashion, these resources could meet a significant share of the base load power needs of the region, at a competitive cost, resulting in direct economic and environmental benefits. This report is envisioned to be a decision-makers’ guide for assessing key challenges and measures to facilitate expanding geothermal development in LAC. Based on discussions with LAC policymakers, utilities, and developers, several cross-cutting challenges affecting most countries in the region were identified, including: i) addressing geothermal resource risks; ii) mobilizing financing for geothermal development; iii) policy, legal, and regulatory reforms to improve the investment climate; and iv) environmental and social considerations. Based on the World Bank’s own extensive experience in the geothermal sector and drawing upon global and regional experience, this report then presents demonstrated solutions to addressing these key challenges. It showcases an array of measures from around the world that clients in LAC can customize for application in their own domestic markets.